Targeting triglyceride/fatty acid cycling in β-cells as a therapy for augmenting glucose-stimulated insulin secretion. - Cantley, J; Biden, T (2010)
Insulin secretion from pancreatic β-cells is triggered by signals arising from the metabolism of glucose and acting through separate initiation and amplification pathways. Despite decades of investigation, crucial details of this mechanism remain poorly understood, especially those relating to the amplifying pathway(s). Advances in this area are vital if we are to understand why insulin secretion fails in type 2 diabetes and to develop strategies to overcome this failure. Indeed, targeting the amplifying pathway(s) would constitute an attractive therapy for augmenting insulin secretion because it would closely link secretory responsiveness to the prevailing glycaemia. It is therefore noteworthy that the possibility of augmenting the amplification pathway(s) has recently been highlighted by studies investigating a metabolic cycle that links the breakdown of triacylglycerol (TAG), release of fatty acid (FA), and subsequent re-incorporation of that FA into TAG. This work reinvigorates and extends the long-standing idea that partitioning of endogenous lipid metabolism towards esterification products promotes the amplification phase of the secretory response. These conceptual advances, and their possible therapeutic application, will be discussed in the following article.